Active Ageing: Social and Cultural Integration of Older Turkish Alevi Refugees in London. Issue 1 (2nd January 2016) - Oglak, Sema; Hussein, Shereen
Abstract: Ageing of migrants in Europe has become an important policy issue, especially within the context of health inequalities and increasing health care costs. Based on in-depth interviews with older Alevi/Kurdish refugees in London, we explore the cumulative impact of difficult migration trajectories on the experience of ageing. The findings highlight the important role of cultural capital and transnational ties throughout the refugees' migration journeys and particularly at old age. However, the study indicates the double edge impact of strong 'solidarity' bonds, increasing isolation at old age due to lack of accumulation of capital and knowledge, particularly language, which are important in accessing health and social care services at old age.